Sustainable Tourism Development : Balancing Growth and Conservation in Southeast Asia - Ivanka Mavrodieva; Nikolay Nenovsky; Ekaterina Stoykova (International Forum of Researchers and Lecturers, 2024)
This paper explores sustainable tourism practices in Southeast Asia, focusing on the interplay between economic growth and environmental conservation. The study employs a case study approach to assess the effectiveness of eco-tourism initiatives in Thailand, Indonesia, and Malaysia. Findings indicate that community-based tourism and stringent environmental regulations are key to achieving sustainability. Policy implications for governments and industry stakeholders are discussed.